2011
DOI: 10.1037/a0023861
|View full text |Cite
|
Sign up to set email alerts
|

Effects of intranasal oxytocin on 'compassion focused imagery'.

Abstract: This study explored the effects of oxytocin on Compassion Focused Imagery (CFI), that is, imagining another "mind" being deeply compassionate to oneself, and the interaction of these effects with self-criticism and feeling socially safe with others. Forty-four healthy participants (29 men and 15 women) completed self-report measures of self-criticism, attachment style, and social safeness before taking part in a double-blind randomized placebo controlled study. They attended two imagery sessions, receiving oxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
104
0
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 113 publications
(109 citation statements)
references
References 66 publications
(81 reference statements)
3
104
0
2
Order By: Relevance
“…A growing body of research demonstrates that for those higher in self-criticism, initial therapeutic interventions can prove threatening (Gilbert et al, 2006;Rockliff et al, 2008, Longe et al, 2011Rockliff et al, 2011;McEwan and Gilbert, 2016). This is despite such therapeutic interventions (e.g.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…A growing body of research demonstrates that for those higher in self-criticism, initial therapeutic interventions can prove threatening (Gilbert et al, 2006;Rockliff et al, 2008, Longe et al, 2011Rockliff et al, 2011;McEwan and Gilbert, 2016). This is despite such therapeutic interventions (e.g.…”
Section: Discussionmentioning
confidence: 91%
“…Considering this, stimulating more positive affiliative processes has been recommended as a therapeutic intervention for those higher in self-criticism, with increasing evidence of the effectiveness of this approach (Gilbert and Procter, 2006; Fredrickson et al, 2008; Hutcherson et al, 2008; Laithwaite, et al, 2008; Beaumont et al, 2012; Judge et al, 2012; Braehler et al, 2013). However, recent research has shown that individuals with higher levels of self-criticism can often be resistant to, or fear, affiliative signals (Gilbert et al, 2011). For example, individuals higher in self-criticism are more likely to have negative reactions to oxytocin -a neuropeptide associated with supportive relationship interactions (Rockliff et al, 2011).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, self-critics can respond to compassionate imagery with threat responses as measured by reduced heart rate variability [66], greater amygdala activation [67] and are less likely to have pleasurable affiliative experiences to compassion imagery when given oxytocin [68]. In fact, as noted above, when self-critical people are invited to focus on feeling connected and being open to receiving compassion, care and concern from others, this often stimulates feelings of grief or an awareness of "how lonely one feels", and/or a sense of not deserving compassion [68].…”
Section: Fears Blocks and Resistances To Compassionmentioning
confidence: 99%